Pengaruh Kepercayaan, Kepuasan Pelanggan dan Komitmen Hubungan terhadap Citra Rumah Sakit di Kota Blitar - Muchlis, Muhammad; Dewanto, Aryo (Universitas Brawijaya, Indonesia, 2013)
This study aimed to determine the influence of the trust, customer satisfaction, and relationship commitment on the hospital image in Blitar city. The research was a cross-sectional study. The respondent of the study were 122 patients who were hospitalized between April to May 2013 or their families in three hospitals in Blitar city. The samples were taken using purposive sampling technique. In this research, the variables were trust, customer satisfaction, and relationship commitment as the independent variables and hospital image as the dependent variable. Data were collected by questionnaires and measured with a scale of Likert 5 levels. Data were analyzed using the multiple linear regression. The results showed that the trust, customer satisfaction, and relationship commitment influence either partially or simultaneously to the hospital image. Customer satisfaction was a dominant variable compared of trust and relationship commitment.